Kenya National Policies and Strategies Seminar Series: Leveraging the New Bottom-Up Economic Plan for Food System Transformation: Video - International Food Policy Research Institute; Kenya Institute for Public Policy Research and Analysis; International Livestock Research Institute (International Food Policy Research Institute, 2022)
Kenya NPS Seminar Series: Leveraging the New Bottom-Up Economic Plan for Food System Transformation in Kenya. Co-organized by IFPRI, CGIAR Initiative on National Policies and Strategies, and KIPPRA. December 5, 2022 • 14:00 - 16:00 PM EAT